Population aging and continued education - Regina T. Riphahn; Parvati Trübswetter (Institute for the Study of Labor (IZA), 2006)
This study investigates whether the incidence of continued vocational education has changed as the German workforce commenced an aging process which is expected to intensify. As the lifespan in productive employment, lengthens human capital investments for older workers become increasingly worthwhile. Using the data of a German population survey we describe recent trends in the development of human capital investments and apply decomposition procedures to the probability of continued education. Holding everything else constant the shift in the population age distribution by itself would have led to a decline in training participation over the considered period, 1996-2004. However, the decomposition analyses yield that behavioral changes caused an increase in training particularly among older workers.
urn:nbn:de:101:1-20090309136
Keywords: 330